With which clothes will I go? A brazilian profile of skin consumption in the game League of Legends (Simbiótica. Revista Eletrônica, 2025)
In online videogame environments, the purchase of virtual goods, while highlighting new forms of consumption, reproduces the search for status, prestige and social differentiation between individuals. The present work carries out a study on the phenomenon of skin consumption in the games League of Legends and League of Legends: Wild Rift, seeking to understand how the dynamics of digital sociability between players are influenced by the consumption of these virtual goods. To achieve the proposed objectives, a bibliographical research was carried out on the topics in question and quantitative data was collected from an online survey form with Brazilian players from all over the country to identify the main motivations that leads them to acquire virtual goods of this type and how the consumption of skins is used as a mediating agent of the sociability established between the subjects in these two games from the north-american company Riot Games.
Keywords: skins; digital sociability; videogames; League of Legends